Anaplastic thyroid carcinoma diagnosed after treatment of lenvatinib for papillary thyroid carcinoma. (1st October 2019) - Yamazaki, Haruhiko; Iwasaki, Hiroyuki; Suganuma, Nobuyasu; Toda, Soji; Masudo, Katsuhiko; Nakayama, Hirotaka; Rino, Yasushi; Masuda, Munetaka
Abstract : Summary: Anaplastic transformation of a primary thyroid tumor whose process can be followed is rare. The objective this study is to report a case of anaplastic transformation of locally advanced papillary thyroid carcinoma after treatment with lenvatinib. A 74-year-old woman consulted a local physician because of cough and bloody sputum. Thyroid cancer with tracheal invasion was suspected on computed tomography (CT) imaging, and she visited our hospital for treatment. We suspected anaplastic thyroid cancer (ATC) and core needle biopsy was performed. Histologic sections of the core needle biopsy showed that the tumor formed a papillary structure, and we diagnosed papillary thyroid carcinoma. Surgery would have been difficult, and we initiated lenvatinib at a low dose of 8 mg/day. CT on day 40 of lenvatinib treatment revealed that the thyroid tumor had shrunk remarkably. CT on day 111 revealed that tumor regrowth and tracheal invasion had been exacerbated. Core needle biopsy was performed, and histologic sections of the core needle biopsy that was performed after regrowth of the tumor showed that individual cancer cells had large, irregular nuclei, and necrosis was also observed. The immunohistochemical findings were negative for thyroglobulin, and only a few cells were positive for thyroid transcription factor 1, and we diagnosed ATC. Anaplastic transformation of the target lesion may be one of the causes of lenvatinib treatment failure in differentiated thyroid carcinoma. Learning points: Anaplastic transformation of a primary thyroid tumor whose process can be followed is rare. The resistance mechanism of lenvatinib in treatment for differentiated thyroid carcinoma has not been clarified. Anaplastic transformation of the target lesion may be one of the causes of lenvatinib treatment failure in differentiated thyroid carcinoma.